GLOBAL PRACTICES OF STUDENTS’ RESEARCH - Maria Fedorova (Obrazovanie i Nauka)
The aim of the study is to consider the problem of students’ research both worldwide and in Russia.Methods. The methods involve review and analysis of the foreign and Russian scientific literature on studied subjects; surveys on the management and realisation of student’s scientific activity in different countries; comparative analysis of the data received during surveys.Results and scientific novelty. At the first stage literature concerning the question of doing research in different countries is analyzed. Then the problems existing in the sphere of students’ research worldwide are identified. Among them are students’ motivation, supervisors’ motivation, developing friendly scientific environment at various levels, communication in science. Then, two surveys were held to support the theoretical issues. The first concerned general aspects of students’ research internationally such as when they start doing it, how they are motivated, what are the relations with supervisors etc. The second included questions about general age of getting scientific degrees (bachelor, master, and PhD), and was divided into two parts: for international and Russian staff. Procedures and results of the surveys undertaken for revealing of scientists’ opinion on quality and features of the specified kind of students’ activity in different countries across the world are described. It is shown, that some problems are common for Russia and global scientific society.Practical significance. On the basis of world experience, some solutions on development of scientific activity of the Russian students have been proposed by the author.